Comparing plant protein sources in two Canadian strains of Arctic charr (Salvelinus alpinus) at the juvenile and grower stages - Smith, Amanda A. (University of Guelph, 2015)
Two feeding trials were performed examining the effects of graded levels of soybean meal and sunflower meal on the performance and health of two genetic strains of Arctic charr (Salvelinus alpinus), one diploid and one triploid, at the juvenile and grower stages. Results at the juvenile stage revealed significant difference between strains in terms of feed intake, feed efficiency, nitrogen retention, and carcass lipid content, but similar response in these parameters to increasing plant protein ingredients in both strains. At the grower stage, weight gain, growth rate, and distal intestine villus length and width were significantly reduced with increasing soybean meal, but not sunflower meal inclusion. Histological examination of the distal intestine at the grower stage revealed several of the classical symptoms of non-infectious enteritis pathologies in fish fed soybean meal, but not in the fish fed sunflower meal. Atlantic Canada Opportunities Agency Atlantic Innovation Fund Canada-Manitoba Agri-Food Research and Development Initiative New Brunswick Department of Agriculture, Aquaculture and Fisheries Natural Sciences and Engineering Research Council of Canada